2014
DOI: 10.1136/injuryprev-2013-041129
|View full text |Cite
|
Sign up to set email alerts
|

Why has the pedestrian death rate decreased in Spain between 1993 and 2011? An application of the decomposition method

Abstract: A decomposition procedure was used to estimate the percentage contributions of exposure, risk of collision and fatality to explain the decreases in pedestrian collision death rates observed in Spain from 1993 to 2011. Information was obtained from the Spanish National Institute of Statistics and the Spanish Register of Road Crashes with Victims. A quasi-induced method was used to obtain estimates of annual pedestrian exposure. Poisson regression was used to obtain age-adjusted and sex-adjusted estimates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…In most cases, the etiology of neurological disorders is likely to be complex and involve an interplay between demographic and non-demographic factors. Decomposition method has been utilized to determine the relative contributions of exposures to differences in mortality rates among different groups of people (12,26). In this study, we employed the decomposition method to quantitatively identify the contributions of demographic or non-demographic factors to the changing trend of mortality rates due to neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the etiology of neurological disorders is likely to be complex and involve an interplay between demographic and non-demographic factors. Decomposition method has been utilized to determine the relative contributions of exposures to differences in mortality rates among different groups of people (12,26). In this study, we employed the decomposition method to quantitatively identify the contributions of demographic or non-demographic factors to the changing trend of mortality rates due to neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…11 In Iran, there was a 20% decrease between 2009 and 2015, with an average decrease of 4% per annum.12 In Spain, the crude pedestrian mortality coefficient fell by 67% between 1993 and 2011. 13 In Brazil, when comparing the year 2000 with the year 2010, a study of traffic accident mortality coefficients and population size found a reduction in changes in the risk of pedestrian mortality in the majority of the country's states. The highest coefficients were found in municipalities with between 100,000 and 500,000 inhabitants in 2000, and in those with more than 500,000 inhabitants in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Od strane mnogih stručnjaka koji se bave ovom sudskomedicinskom problematikom preporučuje se neophodnost veoma pažljivog razmatranja kriterijuma koji se primenjuju u ovakvim istraživanjima, kao i dodatnih obeležja koja utiču na dinamiku i mehanizam povređivanja [8,9,18]. Ova oblast forenzičkih istraživanja je izazov i inspiracija velikom broju autora [4,5,8,9,18].…”
Section: Tabela 1 Struktura Ispitanika Uključenih U Istraživanjeunclassified
“…Ova oblast forenzičkih istraživanja je izazov i inspiracija velikom broju autora [4,5,8,9,18]. B. Karger i saradnici [12] navode 3 kriterijuma u utvrđivanju mehanizma povređivanja koji obezbeđuju neophodan uslov da je DISKUSIJA / / lokalizacija primarnog kontakta obavezno ispod tačke teži-šta tela (centra gravitacije): 1.…”
Section: Tabela 1 Struktura Ispitanika Uključenih U Istraživanjeunclassified
See 1 more Smart Citation